Managing your team through change - Newton, Richard, 1964- (Brillant, 2015)
How do you make change work? What skills and resources do you need? From understanding and planning, to implementing and assessing the impact, this book covers all aspects of managing change using simple, practical steps and strategies, each one of which has been developed, tested and proven to work. Brilliant Managing your Team through Change w.